Increasing retail sales - Shibuchikova Асем (Рroblems of engineering and professional education, 2023)
Merchandising is a new direction in marketing, the popularity of which has been constantly growing in recent years. This is due to the fact that there have been major changes in the motivation of consumer behavior, in particular, a new generation of consumers has formed who are fully aware of and use their rights to information when choosing goods and to guaranteed access to their diversity at competitive prices.